I hunt killers - Lyga, Barry (Lyga, Barry. I hunt killers trilogy, 2012)
Seventeen-year-old Jazz learned all about being a serial killer from his notorious "Dear Old Dad," but believes he has a conscience that will help fight his own urges and right some of his father's wrongs, so he secretly helps the police apprehend the town's newest murderer, "The Impressionist."